Investment in education and its impact on economy of nepal (An empirical analysis of educational spending to agriculture productivity) - Bhattarai, Dhruba; Shrestha, Devendra Prasad (Journal of Advanced Academic Research, 2017)
Using 20 years of time series data, 1994 -2014 , on key macro-economic variables the present paper attempts to examine the significance of public spending in education in GDP through agriculture technical education. We argue that education plays a crucial role in the adaptation of new agriculture technology and methodologies through the availability of more trained agriculture Agriculture manpower including extension workers and thereby help increase agriculture productivity. The increase in agriculture productivity eventually helps to increase the GDP of the country. Results from our econometric analyses revealed that variables like students enrollment in agriculture and forestry institute and agriculture output ratio in GDP are not in expected direction though this one is statistically significant. The result thus signifies that the impact of investment in education especially in agriculture and forestry technical education is inconclusive demanding more deeper analysis is about the possible mechanism of the nexus between the two.